Bile acid metabolic remodeling induced by foodborne contaminants: Mechanistic interfaces and implications for food safety risk assessment - Mengmeng Chen; Jing Cao; Shiyao Fu; Ying Han; Jianping Chen; Xin Yang; Jing Wang (Trends in Food Science & Technology, 2026)

Suspension oxidative roasting for enhanced gold leaching from a quartz-rich refractory gold ore: Process optimization and microstructural evolution - Yan Song; Jianping Jin; Yanjun Li; Bing Zhao; Min Sun; Yuexin Han (Minerals Engineering, 2026)

Oxygen-controlled arsenic volatilization during preheating and preoxidation roasting of carbon–arsenic refractory gold ore - Hua Dong; Jianping Jin; Xinran Zhu; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Provenance evolution, drainage dynamics and depocenter migration: Insights from a comparison between the West African rift basins and the West Asian Tethyan ocean since the Cenomanian - Mohammed Rabiu; Liangliang Wang; Xu Han; Liming Dai; Xianzhi Cao; Yanhui Suo; Sanzhong Li; Jianping Zhou (Journal of Asian Earth Sciences, 2026)

Peak and residual displacement-based design method for enhancing seismic performance of bridge bents retrofitted with BRBs - Yan Shi; Qianzhan Cheng; Jianping Han; Jixin Wang; Yu Ding (Engineering Structures, 2026)

Preparation of coal gasification coarse slag-based low-carbon cementitious materials based on supersulfated cement system: matching mechanism between reaction path induced by multi-mineral salts and mechanical properties - Xiaowei Ge; Xiaowei Gu; Ziyang Hu; Shenyu Wang; Xu Wang; Shaoqian Liu; Xuecheng Ding; Jinchi Han; Jianping Liu; Hao Wang; Xuemei Liu (Chemical Engineering Journal, 2026)

CaMYB30 positively activate the expression of CaWRKY29 and regulates salt stress via modulating ROS homeostasis in pepper (Capsicum annuum L.) - Liping Qiu; Huibin Han; Yue Wang; Yongkang Hu; Lu Zhang; Hui Li; Yufang Wen; Yun Yu; Chao Ji; Jianping Liu (Plant Science, 2026)

Hydrogeochemical insights into the salinization and sustainable development of surface and subsurface water in a typical hyper-arid watershed on Tibetan Plateau - Yuqing Zhang; Yong Xiao; Xu Guo; Jiahao Liu; Jianping Wang; Liang Chang; Jibin Han; Nuan Yang; Zexue Qi; Xiaofan Gu; Jing Ning (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

A systematic review of sphalerite flotation collectors: Mechanisms, progress and prospects - Xiaolong Yu; Jianping Jin; Mingxing Wang; Zhe Bai; Yuexin Han (Minerals Engineering, 2026)

Solar-driven interfacial evaporation technology: Breaking through the performance bottlenecks and challenges from the laboratory to practical application - Huining Zhang; Sen Zhang; Jiyan Li; Yan Wang; Shaofeng Wang; Jianping Han; Yakun Dong; Yue Zhang (Journal of Environmental Chemical Engineering, 2026)

Lambda-cyhalothrin exposure disrupts microbiota-associated bile acid metabolism and enterohepatic feedback in mice - Mengmeng Chen; Jing Cao; Shiyao Fu; Ying Han; Weijia Zheng; Jianping Chen; Xin Yang; Jing Wang (Environmental Pollution, 2026)

Development of a frost-specific module and its integration into a process-based model for winter wheat frost damage simulation - Yuanda Zhang; Peijuan Wang; Yuping Ma; Lin Cheng; Yang Li; Dianchen Han; Dingrong Wu; Shuxian Liu; Jianping Guo (Agricultural and Forest Meteorology, 2026)

Molecular authentication of Polyporus umbellatus and its commercial products using a nucleotide signature - Junrong Wang; Yongmei Xing; Huilin Yuan; Yiyun Fan; Jianping Han; Xiaohui Pang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Root oxygen governs dryland ecosystem stability - Dongliang Han; Lei Ding; Guolong Zhang; Jianping Huang; Li Fu; Ming Peng; Changyu Li; Xiaoyue Liu (Plant and Soil, 2026)

Kinetic mechanism and structural evolution during blank roasting of vanadium-bearing shale - Xiaolong Yu; Jianping Jin; Xinran Zhu; Zhe Bai; Shuaihou Yang; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Construction of an EDTA-assisted biochar-supported nanoscale zero-valent iron catalyst from betel nut shell and blast furnace dust for enhanced H2O2 generation and Fenton-like degradation of 4-fluorophenol - Huining Zhang; Zongqian Zhang; Jiawen Sun; Jianping Han; Yi Zhao; Zhiqiang Wei; Zhiguo Wu; Shaofeng Wang; Yan Wang; Yue Zhang; Yankui Xiao (Journal of Environmental Management, 2026)

Determining the sustainable brine extraction threshold in Qarhan Salt Lake via numerical simulation under multi-constraints - Han Jibin; Ma Hongkui; Han Wenhua; Ma Zhe; Huo Yurui; Zhang Luxi; Jiang Hongchen; Xiao Yong; Wang Jianping (Groundwater for Sustainable Development, 2026)

Optimal design and performance evaluation of outrigger systems augmented with tuned viscous mass dampers - Dawei Li; Jianting Wang; Kangqian Xu; Jianping Han; Yonggang Gao (Bulletin of Earthquake Engineering, 2026)

Hydrogen-based fluidized bed reduction of limonitic laterite nickel ore: towards co-recovery of iron and nickel and metallization enhancement - Jiaqi Wang; Yanjun Li; Jianwen Yu; Yuexin Han; Jianping Jin (Minerals Engineering, 2026)

Advances in pyrite depressants for Low-Alkalinity flotation Systems: Mechanisms, Strategies, and future directions - Xiaolong Yu; Hui Li; Bing Zhao; Zhe Bai; Jianping Jin; Yuexin Han (Minerals Engineering, 2026)

Substrate source and mineral protection synergistically govern the temperature response of lake sediment organic carbon - Beichen Wang; Xiaoxi Sun; Zhen Yang; Xinyi Li; Min Cai; Bingfu Yao; Li Liu; Tianran Sun; Jian Yang; Jibin Han; Xiying Zhang; Jianping Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

The liver-bone axis: an emerging player in disease pathogenesis and therapeutic intervention - Shenqi Han; Yi Wei; Guanxing Yu; Wenlong Jia; Wei Liao; Yi He; Kun Cheng; Jianping Zhao; Shuai Xiang; Wanguang Zhang; Xiaoping Chen; Bixiang Zhang; et al. (Science China Life Sciences, 2026)

A precise global ionospheric total electron content forecasting model based on multi-neural network ensemble - Huan Zhang; Yuanyi Han; Mengzhu Peng; Bao Zhang; Chaoqian Xu; Cheng Huang; Feifei Tang; Jian Kong; Yibin Yao; Jianping Pan; He Huang; Hongming Li; et al. (GPS Solutions, 2026)

Hydrogen-based suspension roasting for efficient utilization of high-phosphorus oolitic hematite: Selective reduction mechanism and metallization behavior - Xuesong Sun; Yanjun Li; Zhidong Tang; Jianwen Yu; Yize Guo; Jianping Jin; Yuexin Han (Minerals Engineering, 2026)

Reconfiguring antisense RNA-mediated replication enables modular and autonomous plasmid copy number control - Gege Wang; Jianping Xu; Tengfei Zhao; Qi Wang; Yuanfei Han; Zhiyong Cui; Qingsheng Qi; Qian Wang (Chemical Engineering Journal, 2026)

Withanolides from Physalis minima as potential anti-inflammatory agents: From isolation to in vitro and in vivo validation - Jiangping Wu; Shihan He; Zhu Yang; Jianping Zhao; Yiping Yang; Qiangbao Xu; Juan Feng; Qiuyue Lv; Zhongmei Zou; Jun Han (Phytochemistry, 2026)

Microbial bioleaching and biofixation of vanadium from smelting ash using Bacillus subtilis - Jianping Lu; Han Zhang; Zhongjun Shen; Yifan Chen; Baogang Zhang (Journal of Water Process Engineering, 2026)

Evolution and diffusion of the digital and intelligent transformation for safety emergency in coal mining enterprises under subsidy mechanisms - Jianping Shang; Quanlong Liu; Jingzhi Wang; Hui Han (Environment, Development and Sustainability, 2026)

CO2-enhanced siderite ore self-magnetization roasting for iron recovery: experimental optimization and mechanism analysis - Tingbo Zhou; Yongshen Sun; Yuexin Han; Jianping Jin (Minerals Engineering, 2026)

Closing the loop on nanoplastic pollution: A 3D printed coral-like adsorbent enabling cyclic adsorption and ice-crystal catalytic degradation for waste minimization - Huining Zhang; Yakun Dong; Baixiang Wang; Jianping Han; Wenhui Niu; Yi Zhao (Journal of Cleaner Production, 2026)

Using DNA metabarcoding to monitor key factors affecting the fungal community in Licorice: collection site, processing method, and storage condition - Yanan Xu; Junrong Wang; Chune Fan; Huilin Yuan; Meihua Yang; Jianping Han; Xiaohui Pang (Food Research International, 2026)

Quantitative inversion of soil salinization in salt lake regions: Spatiotemporal variation and driving mechanisms - Jinjun Han; Zitao Wang; Jianping Wang; Chuntao Zhao; Dongmei Yu; Zhaofeng Liu (Journal of Geographical Sciences, 2026)

CaWRKY6-CaERF3 regulate ROS homeostasis to positively modulate salt stress in pepper (Capsicum annuum L.) - Zhimin Li; Huibin Han; Hui Li; Zhen An; Yue Wang; Yufang Wen; Liping Qiu; Chao Ji; Qinghong Zhou; Jianping Liu (Plant Cell Reports, 2026)

Statistical characterization of low-frequency seabed ambient noise on the southwest Indian ridge based on passive acoustic observations - Ningte Chen; Jianping Zhou; Chenhua Han; Huawei Qin; Minhui Zheng (Marine Pollution Bulletin, 2026)

Corrigendum to “Constant-strength ductility factor spectra of SDOF system considering SSI effects subjected to ground motions of the 2023 Mw 7.7 Pazarcık earthquake” [Soil Dynam Earthq Eng 200 (2026) 109874] - Yan Shi; Zhuoli He; Jianping Han; Yu Ding; Hongguo Qin (Soil Dynamics and Earthquake Engineering, 2026)

Constant-strength ductility factor spectra of SDOF system considering SSI effects subjected to ground motions of the 2023 Mw 7.7 Pazarcık earthquake - Yan Shi; Zhuoli He; Jianping Han; Yu Ding; Hongguo Qin (Soil Dynamics and Earthquake Engineering, 2026)

Hysteretic behavior of a novel self-centering beam-column joint with enhanced resilience - Jianjun Wang; Jianping Han; Jixiang Xu (Engineering Structures, 2026)

Paleomagnetic inclination correction for the Upper Jurassic Penglaizhen Formation red beds from the Sichuan basin, South China Block: Implications for paleogeographic reconstruction - Yunchuan Xu; Xiaodong Tan; Bo Ran; Zhi Wang; Yulin Han; Yuyue Han; Zihao Wang; Jianping Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Semi-industrial test of vanadium extraction from stone coal vanadium ore by high-pressure roll-suspension roasting-solidification leaching process - Zhe Bai; Zhiming Li; Tingbo Zhou; Mingxing Wang; Shuai Yuan; Yuexin Han; Jianping Jin (Minerals Engineering, 2025)

Sustainable exploitation of siderite ore using fluidization roasting technology without reductant - Yuchao Qiu; Xinran Zhu; Jianping Jin; Yuexin Han; Yuwen Tao; Chenghao Lu (Minerals Engineering, 2025)

Preparation of BiVO4/BiOI/ACF photocatalysts and their adsorption-photocatalytic synergistic degradation of phenol - Huining Zhang; Zongqian Zhang; Lihong Tian; Jianping Han; Yi Zhao; Zhiqiang Wei; Zhiguo Wu; Yang Cao (Journal of Water Process Engineering, 2025)

Soil extracellular enzyme stoichiometry reveals the nutrient limitations of soil microbial metabolism under precipitation changes in Ningxia desert steppe of China - Jiali Lian; Jing Chen; Cui Han; Ying Zhao; Xueqin Yang; Jianping Li (European Journal of Soil Biology, 2025)

Metal-bridged self-assembly of recognition-functionalized MCOFs for ultrasensitive photoelectrochemical sensing of perfluorooctanoic acid - Xionghui Ma; Wenwen Cao; Rui Chen; He Yu; Chaohai Pang; Zhongsheng Yi; Yuhao Xiong; Bingjun Han; Zhi Xu; Jianping Li; Shuhuai Li (Chemical Engineering Journal, 2025)

A review of electrocatalyst design for the selective oxidation of alcohols to carboxylic acids - Jiaxuan Zhou; Yaodong Yu; Jiani Han; Jianping Lai; Lei Wang (Chemical Engineering Journal, 2025)

Carbon footprint assessment and emission reduction analysis of wood flooring based on life-cycle assessment: six cases from China - Jia Guo; Haigang Wang; Luqing Gao; Han Zhu; Daxin Liang; Zefang Xiao; Yonggui Wang; Wenyan Jing; Jianping Pan; Yanjun Xie (Clean Technologies and Environmental Policy, 2025)

Characterization of meteorological and agricultural drought for summer maize and its climatic drivers - Yuanda Zhang; Peijuan Wang; Yang Li; Dianchen Han; Dingrong Wu; Shuxian Liu; Jianping Guo (Atmospheric Research, 2025)

Food-derived bioactive peptides: health benefits, structure–activity relationships, and translational prospects - Hongda Chen; Jiabei Sun; Haolie Fang; Yuanyuan Lin; Han Wu; Dongqiang Lin; Zhijian Yang; Quan Zhou; Bingxiang Zhao; Tianhua Zhou; Jianping Wu; Shanshan Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Tailoring sulfur reactivity in ReS2 via d–p orbital hybridization for efficient hydrogen production - Yinglong Weng; Yingbo Kang; Nannan Li; Tingyu Du; Li Jin; Jianping Zhang; Jin Yong Lee; Xiaotong Han (Chemical Engineering Journal, 2025)

Microbial diversity outweighs plant diversity in mediating the response of ecosystem multifunctionality to altered precipitation in a desert steppe - Cui Han; Yi Zhang; Xu Luo; Ying Zhao; Xueqin Yang; Jiali Lian; Jianping Li (Plant and Soil, 2025)

Pore–Fracture Connectivity of High-Rank Coal in Qinshui Basin, China - Lei Han; Dongxiang Huang; Zhouyang Qiu; Jian Shen; Xiaodong Zhang; Xiaoming Ni; Zhenfeng Yu; Jianping Bai; Jindong Yang (Natural Resources Research, 2025)

Microbial inoculant and microalgae fertilizer improved the growth and quality of Salvia miltiorrhiza cultivated in lead-contaminated soil - Ying Ren; Gang Wang; Yuying Su; Jinfeng Li; Hui Zhang; Meihua Yang; Jianping Han (Applied Soil Ecology, 2025)

An overview of extreme weather-epidemic compound disasters - Jianping Huang; Xinbo Lian; Huijun Wang; Tong Zhu; Han Li; Yingjie Zhao; Rui Wang; Danfeng Wang; Wei Yan; Shujuan Hu; Xiaodan Guan; Shanshan Wang (Science Bulletin, 2025)

Unraveling the distinct response patterns of abundant and rare fungi to vanadium at nationwide smelting sites - Han Zhang; Baogang Zhang; Jianping Lu; Wenyue Yan; Yang Tang; Bo Jiang; Yi Xing (Journal of Hazardous Materials, 2025)

The effect and mechanism analysis of calcium and magnesium between the blank roasting-leaching process of vanadium shale - Jianping Jin; Xiaolong Yu; Zhe Bai; Zhenya Zhou; Yuexin Han; Yanjun Li (Fuel, 2025)

Multi-objective optimization for brine mining and water balance in the Qarhan Salt Lake, Qaidam Basin - Jibin Han; Jianping Wang; Liye Li; Dongmei Yu; Hongkui Ma; Luxi Zhang; Hongchen Jiang (Journal of Environmental Management, 2025)

Vanadium extraction process and technology from strategic vanadium-bearing shale: A review - Zhe Bai; Jiahao He; Yuexin Han; Yongsheng Sun; Shuai Yuan; Jianping Jin (Fuel, 2025)

Hierarchical Joint Elastic Full Waveform Inversion Based on Wavefield Separation for Marine Seismic Data - Guowang Han; Yuanyuan Li; Jianping Huang (Journal of Marine Science and Engineering, 2025)
In marine seismic surveys, towed streamers record only pressure data with limited offsets and insufficient low-frequency content, whereas Ocean Bottom Nodes (OBNs) acquire multi-component data with wider offset and sufficient low-frequency content, albeit with sparser spatial sampling. Elastic full waveform inversion (EFWI) is used to estimate subsurface elastic properties by matching observed and synthetic data. However, using only towed streamer data makes it impossible to reliably estimate shear-wave velocities due to the absence of direct S-wave recordings and limited illumination. Inversion using OBN data is prone to acquisition footprint artifacts. To overcome these challenges, we propose a hierarchical joint inversion method based on P- and S-wave separation (PS-JFWI). We first derive novel acoustic-elastic coupled equations based on wavefield separation. Then, we design a two-stage inversion framework. In Stage I, we use OBN data to jointly update the P- and S-wave velocity models. In Stage II, we apply a gradient decoupling algorithm: we construct the P-wave velocity gradient by combining the gradient using PP-waves from both towed streamer and OBN data and construct the S-wave velocity gradient using the gradient using PS-waves. Numerical experiments demonstrate that the proposed method enhances the inversion accuracy of both velocity models compared with single-source and conventional joint inversion methods.

Atypical sulfur-containing physalin from Physalis minima and protective effect against ischemia-reperfusion injury - Jiangping Wu; Zixu Li; Jianping Zhao; Tao Zhang; Jun Zhang; Qiuyue Lv; Jiangfei Li; Guodong Wang; Jun Han; Zhongmei Zou (Phytochemistry, 2025)

d–p orbitals hybridization triggered electron pumping in Fe–O–Mo bridged structure for efficient water electrolysis - Jianping Zhang; Yinglong Weng; Tingting Huang; Xiaotong Han; Ho Seok Park (Chemical Engineering Journal, 2025)

Towards clean energy technologies: Assessing the supply potential of critical rare earth elements in China - Han Ding; Jianping Ge (The Extractive Industries and Society, 2025)

Impact of pulsed electric field pretreatment on protein and its binding with sodium ions in brined beef - Yuchen Guo; Tian Chen; Songmei Hu; Jianping Yue; Xiaobo Yu; Xinglian Xu; Minyi Han (Innovative Food Science & Emerging Technologies, 2025)

Rapid damage assessment and rotation angle model of EEP-HSSBC connections under post-fire earthquake using machine learning - Jixiang Xu; Yifan Zhang; Jianping Han (Engineering Structures, 2025)

Experimental investigation on the seismic performance of T-shaped connected modular beam-column connection - Jixiang Xu; Jizong Liang; Jianping Han; Yifan Zhang (Engineering Structures, 2025)

Advances in Research on Climate Change and Its Effects on the Arid and Semi-Arid Regions of China over the Past Century - Qiang Zhang; Jianping Huang; Jinhu Yang; Xiaodan Guan; Haipeng Yu; Biao Zhu; Hongli Zhang; Dongliang Han; Xinyang Yan; Guolong Zhang; Zesu Yang; Jian Zeng (Journal of Meteorological Research, 2025)

Flow Variations and Circulation Process of Saline Springs in the Nangqen Basin, Tibetan Plateau - Jibin Han; Jianping Wang; Hongkui Ma; Yongshou Li; Zhao An; Yong Xiao; Wenhua Han; Huaide Cheng; Haizhou Ma; Hongchen Jiang (Journal of Earth Science, 2025)

Abrupt loss of species richness caused by ecosystem transition - Li Fu; Jianping Huang; Guolong Zhang; Dongliang Han; Lei Ding; Yun Wei; Xiaoyue Liu; Changyu Li; Haipeng Yu (Science Bulletin, 2025)

Iron induced electronic structure modulation of cobalt hydrogen phosphite for efficient freshwater/seawater splitting - Kun Zhang; Tieshan Zou; Jianping Zhang; Siqiong Wang; Xinyu Liu; Hanlian Yang; Jian Li; Xiaotong Han; Yongsheng Han (Chemical Engineering Journal, 2025)

A peptide-nanoparticle conjugate to steer elimination of drug-resistance bacteria and LPS - Yajie Wang; Han Zhou; Yaodong Liu; Xinqiuyue Wang; Lei Zhang; Jiayang Cai; Yi Chen; Chang Liu; Zimei Wu; Jianping Liu; Wenli Zhang (Chemical Engineering Journal, 2025)

Silent soils have been awakened by climate change - Dongliang Han; Jianping Huang; Xiaoyue Liu; Li Fu; Lei Ding; Guolong Zhang; Changyu Li; Fan Yang; Jinsen Shi; Beidou Zhang (CATENA, 2025)

Plant species richness enhances aboveground primary productivity via net biodiversity effects and bacterial community interactions - Xu Luo; Yingzhong Xie; Shaoli Yue; Mingfan Yang; Cui Han; Yaxin Zhao; Ying Zhao; Jianping Li (Applied Soil Ecology, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Constant-strength residual displacement ratio spectra for SDOF systems with energy-dissipating fuses - Yan Shi; Jixin Wang; Hongguo Qin; Jianping Han; Yunshuai Liu (Soil Dynamics and Earthquake Engineering, 2025)

Study on dispersion process and explosion hazard of propylene oxide/aluminum powder blended fuel under windy conditions - Linghui Zeng; Zhongqi Wang; Zuolin Ouyang; Jiafan Ren; Han Li; Jianping Li (Fuel, 2025)

Synthesis and anti-inflammatory activity of chromone-sulfonamide derivatives as COXs/iNOS dual-target inhibitors - Meng Qin; Tao Xing; Mengdi Zhang; Jiatong Han; Shuyan Yu; Jianping Chen; Yuheng Ma (Medicinal Chemistry Research, 2025)

Desertification dynamics and future projections in Qaidam Basin, China - Jinjun Han; Jianping Wang; Chuntao Zhao; Chao Yue; Zhaofeng Liu (Environmental Monitoring and Assessment, 2025)

Identification and thermal characteristics of linear discontinuities on a high-steep slope using UAV with thermal infrared imager - Wen Zhang; Han Yin; Jianping Chen; Changwei Lu; Tengyue Li; Bo Han; Zihan Zhao; Jia Wang; Junqi Chen (International Journal of Rock Mechanics and Mining Sciences, 2025)

Seismic demand-oriented design of hybrid base-isolated building with the tuned inerter eddy current damper - Dawei Li; He Bai; Yu Lou; Jianping Han (Soil Dynamics and Earthquake Engineering, 2025)

Identification of multiple miRNA-encoded peptide reveals OsmiPEP162a putatively stabilizes OsMIR162 in rice - Jianping Zhou; Rui Zhang; Qinqin Han; Hongjun Yang; Wei Wang; Yibo Wang; Xuelian Zheng; Fan Luo; Guangze Cai; Yong Zhang (Plant Cell Reports, 2025)

Design and optimization of an integrated UF-NF membrane process for treating rare earth refining wastewater - Yiwen Wang; Shuanglin Gui; Qinliang Jiang; Pei Han; Hong Wang; Jianping Deng; Tao Chen; Jianxin Li (Journal of Water Process Engineering, 2024)

Fungal communities in three root herbs: Insights and implications - Yanan Xu; Chune Fan; Huilin Yuan; Yufeng Li; Jianping Han; Meihua Yang; Xiaohui Pang (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Bioinformatics analysis of the mechanisms of traumatic brain injury-associated dementia based on the competing endogenous RNA - Changmeng Cui; Li Zhu; Guangkui Han; Jianping Sun; Liang Zhang; Yujin Guo; Pei Jiang (Psychopharmacology, 2024)

A sustainable and clean method for vanadium extraction from shale ore by suspension oxidation roasting: A comparative study of leaching behavior - Jianping Jin; Zhenya Zhou; Yimin Zhu; Yuexin Han; Sadan Kelebek (Process Safety and Environmental Protection, 2024)

Simultaneous removal of CTRX and Cr(Ⅵ) by CQDs-doped bifunctional molecular imprinted BiOCl/Bi3NbO7 photocatalyst: The enhanced selective performance and charge separation abilities - Huining Zhang; Yankui Xiao; Zongqian Zhang; Jianping Han; Zhiguo Wu; Zhiqiang Wei; Ying Zhu; Qi Guo; Lihong Tian; Yuling Tang (Journal of Environmental Chemical Engineering, 2024)

Hydrogel microspheres for stem cell recruitment and induction of directed differentiation in osteoarthritis therapy - Han Yu; Huanhuan Luo; Jianping Chen; Xiaodong Hu; Yujiong Chen; Jiaqi Zhong; Botao Liu; Yanfang Liu; Gang Chen; Chenglong Huang; Zhaoxiang Peng (Chemical Engineering Journal, 2024)

Nicotinamide Riboside Promotes the Proliferation of Endogenous Neural Stem Cells to Repair Spinal Cord Injury - Jianping Zhang; Jun Shang; Han Ding; Wenxiang Li; Zonghao Li; Zhongze Yuan; Han Zheng; YongFu Lou; Zhijian Wei; Hengxing Zhou; Shiqing Feng; Xiaohong Kong; et al. (Stem Cell Reviews and Reports, 2024)

Strength reduction factor spectra of self-centering SDOF systems with flag-shaped model subjected to offshore ground motions - Yan Shi; Yinhai Pei; Jianping Han; Baokui Chen; Bowei Wang (Soil Dynamics and Earthquake Engineering, 2024)

Geometric searching of 3D critical slip surface of a non-persistent fracture-dominated rock slope - Wen Zhang; Jiali Han; Changwei Lu; Hongcheng Liu; Junqi Chen; Jia Wang; Tengyue Li; Jianping Chen (Computers and Geotechnics, 2024)

Multiscale coupling analysis and modeling of airflow and heat transfer for warehouse-packaging-kiwifruit under forced-air cooling - Qian Chen; Jianping Qian; Han Yang; Jiali Li; Xintao Lin; Baogang Wang (Biosystems Engineering, 2024)

Effect of pulsed electric field (PEF) on NaCl diffusion in beef and consequence on meat quality - Yuchen Guo; Jiahua Gao; Yun Bai; Xia Wang; Xinglian Xu; Xinqing Lu; Jianping Yue; Minyi Han (Meat Science, 2024)

A novel bifunctional particle electrode with abundant Fe/Fe3C and Fe-N-C sites to enhance the performance of electro-Fenton in degrading organic pollutant - Junjie Cheng; Xinman Tu; Li Zhang; Mingzhu Han; Rentao Zhou; Shaohua Luo; Honghu Zeng; Tingting Li; Jianping Zou (Journal of Environmental Chemical Engineering, 2024)

Experimental and numerical study of low-yield-point steel corrugated pipe dampers - Hu Li; Yongfeng Du; Jianping Han; Fangyu Li; Peihong Chi (Soil Dynamics and Earthquake Engineering, 2024)

Response of antioxidant activity, active constituent and rhizosphere microorganisms of Salvia miltiorrhiza to combined application of microbial inoculant, microalgae and biochar under Cu stress - Ying Ren; Gang Wang; Yuying Su; Jinfeng Li; Hui Zhang; Jianping Han (Science of The Total Environment, 2024)

CLV3-CLV1 signaling governs flower primordia outgrowth across environmental temperatures - Yufang Wen; Youxin Yang; Jianping Liu; Huibin Han (Trends in Plant Science, 2024)

Two new sesquiterpene lactones from the branches and leaves of Cinnamomum camphora chvar. Borneol - Zhiyong Xu; Tao Jiang; Wei Xiong; Chuanqi Xie; Yunfei Liu; Xiaodan Han; Xuefang Wen; Jianping Fu; Junwei Xu; Yongsheng Guo; Lei Wu (Phytochemistry Letters, 2024)

A sustainable method for high-efficient exploitation of low-grade vanadium-bearing shale ore by oxidation roasting pretreatment - Xinran Zhu; Shuaihou Yang; Zhenya Zhou; Jianping Jin; Yuexin Han (Journal of Cleaner Production, 2024)

Identification of toxic Gelsemium elegans in processed food and honey based on real-time PCR analysis - Gang Wang; Ying Ren; Yuying Su; Hui Zhang; Jinfeng Li; Hongxia Zhao; Huixia Zhang; Jianping Han (Food Research International, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Research progress on remediation of organochlorine pesticide contamination in soil - Ying Ren; Gang Wang; Xuanjiao Bai; Yuying Su; Zheng Zhang; Jianping Han (Environmental Geochemistry and Health, 2024)

Identification and verification of PCDD/Fs indicators from four typical large-scale municipal solid waste incinerations with large sample size in China - Lijun Liu; Xichao Chen; Wenhua Yin; Hao Wu; Junbin Huang; Yanyan Yang; Zhiqiang Gao; Jinqiong Huang; Jianping Fu; Jinglei Han (Waste Management, 2023)

Critical review on modified floating photocatalysts for emerging contaminants removal from landscape water: problems, methods and mechanism - Xiaoning Fu; Guangzhu Zhou; Jianping Li; Qiuhui Yao; Zuozhen Han; Rongchao Yang; Xi Chen; Yuanhao Wang (Chemosphere, 2023)

Quantifying the late Quaternary incision rate in the upper Jinsha River with dated fluvial terraces and transient tributary profiles - Zhihai Li; Jianping Chen; Zhigang Shan; Yiding Bao; Yuchao Li; Kun Shan; Di Liu; Mengxia Han (CATENA, 2023)

Divergent sensitivity of vegetation to aridity between drylands and humid regions - Guolong Zhang; Yongli He; Jianping Huang; Li Fu; Dongliang Han; Xiaodan Guan; Beidou Zhang (Science of The Total Environment, 2023)

Rapid nondestructive detecting of wheat varieties and mixing ratio by combining hyperspectral imaging and ensemble learning - Xinna Jiang; Youhua Bu; Lipeng Han; Jianping Tian; Xinjun Hu; Xiaobing Zhang; Dan Huang; Huibo Luo (Food Control, 2023)

Heat waves accelerate the spread of infectious diseases - Xinbo Lian; Jianping Huang; Han Li; Yongli He; Zhi Ouyang; Songbo Fu; Yingjie Zhao; Danfeng Wang; Rui Wang; Xiaodan Guan (Environmental Research, 2023)

Effects of Dietary Supplementation with Lactobacillus acidophilus and Bacillus subtilis on Mucosal Immunity and Intestinal Barrier Are Associated with Its Modulation of Gut Metabolites and Microbiota in Late-Phase Laying Hens - Xin Chen; Weiwen Chen; Wenjia Ci; Yingying Zheng; Xinyan Han; Jianping Huang; Jianjin Zhu (Probiotics and Antimicrobial Proteins, 2023)

A dynamic shelf-life prediction method considering actual uncertainty: Application to fresh fruits in long-term cold storage - Qian Chen; Jiali Li; Han Yang; Jianping Qian (Journal of Food Engineering, 2023)

Strength reduction factor spectra for SDOF systems with structural fuses - Yan Shi; Dongsheng Wang; Hongguo Qin; Xiaoyu Chen; Jianping Han; Zhichao Zhang (Soil Dynamics and Earthquake Engineering, 2023)

Concurrent reductive decontamination of chromium (VI) and uranium (VI) in groundwater by Fe(0)-based autotrophic bioprocess - Jianping Lu; Rongyue Geng; Han Zhang; Zhen Yu; Tao Chen; Baogang Zhang (Journal of Hazardous Materials, 2023)

Sequentially modified carbon felt for enhanced p-nitrophenol biodegradation through direct interspecific electron transfer - Yiwen Feng; Jianping Lu; Zhongjun Shen; Jing Li; Han Zhang; Xiaoxin Cao; Zhengfang Ye; Guodong Ji; Qingsong Liu; Yuanan Hu; Baogang Zhang (Journal of Hazardous Materials, 2023)

Mechanism of Reducing the Bursting Liability of Coal using Liquid Nitrogen Cyclic Fracturing - Shuai Chen; Linming Dou; Lei Zhang; Jingbo Song; Jianping Xu; Zepeng Han (Natural Resources Research, 2023)

PM2.5 caused ferroptosis in spermatocyte via overloading iron and disrupting redox homeostasis - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Ying Tang; Chang Liu; Yimeng Wang; Jianping Chen; Xiao Jiang; Huan Yang; Lei Sun; Qing Chen; et al. (Science of The Total Environment, 2023)

Oscillatory biomarkers of autism: evidence from the innate visual fear evoking paradigm - Chuanliang Han; Mingrou Guo; Xiaoyin Ke; Lanting Zeng; Meijia Li; Naem Haihambo; Jianping Lu; Liping Wang; Pengfei Wei (Cognitive Neurodynamics, 2023)

Scale dependency and anisotropy of mechanical properties of jointed rock masses: insights from a numerical study - Yanyan Li; Rui Wang; Jianping Chen; Zhihong Zhang; Kun Li; Xudong Han (Bulletin of Engineering Geology and the Environment, 2023)

Development and validation of a routine blood parameters-based model for screening the occurrence of retinal detachment in high myopia in the context of PPPM - Shengjie Li; Meiyan Li; Jianing Wu; Yingzhu Li; Jianping Han; Wenjun Cao; Xingtao Zhou (EPMA Journal, 2023)

The evolution of ecological security and its drivers in the Yellow River Basin - Guolong Zhang; Jianping Huang; Xiaoyue Liu; Xiaodan Guan; Yun Wei; Lei Ding; Dongliang Han (Environmental Science and Pollution Research, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Gestational exposure to perfluoroalkyl substances is associated with placental DNA methylation and birth size - Hexing Wang; Wenyun Li; Jiaqi Yang; Yuanping Wang; Hongyi Du; Minghui Han; Linji Xu; Shuping Liu; Jianping Yi; Yue Chen; Qingwu Jiang; Gengsheng He (Science of The Total Environment, 2023)

Vanadium extraction from V-bearing shale using oxidation roasting and acid leaching - Xinran Zhu; Zhenya Zhou; Jianping Jin; Yanjun Li; Yuexin Han (Minerals Engineering, 2023)

Seasonal Interaction of River Water-Groundwater-Salt Lake Brine and Its Influence on Water-Salt Balance in the Nalenggele River Catchment in Qaidam Basin, NW China - Jibin Han; Jianxin Xu; Lei Yi; Zheng Chang; Jianping Wang; Haizhou Ma; Baoyun Zhang; Hongchen Jiang (Journal of Earth Science, 2022)

Variations in terrestrial oxygen sources under climate change - Lei Ding; Jianping Huang; Changyu Li; Dongliang Han; Xiaoyue Liu; Haiyun Li; Yan Bai; Jiping Huang (Science China Earth Sciences, 2022)

Bacteriophage therapy in aquaculture: current status and future challenges - Ruyin Liu; Ganghua Han; Zong Li; Shujuan Cun; Bin Hao; Jianping Zhang; Xinchun Liu (Folia Microbiologica, 2022)

Comprehensive analysis of a paleo-landslide damming event on the upper reach of the Jinsha River, SE Tibetan Plateau - Yuchao Li; Jianping Chen; Zhihai Li; Xudong Han; Shijie Zhai; Yongchao Li; Yiwei Zhang; Feifan Gu (Bulletin of Engineering Geology and the Environment, 2022)

Numerical simulation of the Qulong Paleolandslide Dam event in the late pleistocene using the finite volume type shallow water model - Xiaohui Sun; Xudong Han; Jianping Chen; Yiding Bao; Wei Peng (Natural Hazards, 2022)

Intensification of Downslope Nutrient Transport and Associated Biological Responses Over the Northeastern South China Sea During Wind-Driven Downwelling: A Modeling Study - Aiqin Han; Jianping Gan; Minhan Dai; Zhongming Lu; Linlin Liang; Xiaozheng Zhao (Frontiers in Marine Science, 2021)
Coastal downwelling is generally considered to have a limited biological effect compared with coastal upwelling. In this study, downslope transport of nearshore, nutrient-enriched waters during downwelling is found to induce distinct biological productivity in the water column over the northeastern South China Sea (NSCS). By conducting a process-driven study over a widened shelf with intensified downwelling in the NSCS, we investigated the biophysical processes associated with strong nutrient enrichment in the water column of downwelled waters. These processes and underlying mechanisms are largely unreported and remain unclear. Field measurements and a three-dimensional coupled physical-biological model incorporating nitrate ( N ), phytoplankton ( P ), zooplankton ( Z ), and detritus ( D ) were utilized to investigate distinct cross-shore nutrient transport over the uniquely widened NSCS shelf. We revealed that intensified downwelling circulation, dynamically induced by the widened shelf topography, enhanced chlorophyll a and biological productivity in a strip of well-mixed water over the inner shelf as well as in the downwelled water over the mid-shelf. Strong time lags and spatial differences existed among N , P , and Z because of the physical transport and the ensuing biogeochemical response. The intensified downslope transport of nutrient-rich coastal water formed distinct cross-shore wedge-shaped P , Z , and D structures, while N was rapidly consumed in the water column. This study illustrates the underlying coupled physical-biogeochemical processes associated with the observed biogeochemical response to wind-driven downwelling circulation over the variable shelf, which are commonly found in coastal oceans worldwide.

Complete genome sequence of a putative novel ilarvirus isolated from Eleocharis dulcis - Lanqing Lv; Xinyang Wu; Jiajia Weng; Yuchao Lai; Kelei Han; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; et al. (Archives of Virology, 2021)

Seismic inversion-based prediction of the elastic parameters of rocks surrounding roadways: a case study from the Shijiazhuang mining area of North China - Suzhen Shi; Jian Feng; Zuiliang Liu; Youchao Qi; Peifei Duan; Qi Han; Jianping Zuo (Acta Geophysica, 2021)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Atmospheric-Boundary-Layer-Height Variation over Mountainous and Urban Sites in Beijing as Derived from Radar Wind-Profiler Measurements - Raman Solanki; Jianping Guo; Jian Li; Narendra Singh; Xiaoran Guo; Yi Han; Yanmin Lv; Jian Zhang; Boming Liu (Boundary-Layer Meteorology, 2021)

The Significant Role of Radiosonde-measured Cloud-base Height in the Estimation of Cloud Radiative Forcing - Hui Xu; Jianping Guo; Jian Li; Lin Liu; Tianmeng Chen; Xiaoran Guo; Yanmin Lyu; Ding Wang; Yi Han; Qi Chen; Yong Zhang (Advances in Atmospheric Sciences, 2021)

Whole brain volume and cortical thickness abnormalities in Wilson’s disease: a clinical correlation study - Yukun Song; Lin Zou; Jing Zhao; Xiangxue Zhou; Yingqian Huang; Haishan Qiu; Haiwei Han; Zhiyun Yang; Xunhua Li; Xiaoying Tang; Jianping Chu (Brain Imaging and Behavior, 2021)

Comparisons of several methods for landslide susceptibility mapping: case of the Benzilan and Waka Towns, Southwest China - Jianping Chen; Wei Peng; Xiaohui Sun; Qing Wang; Xudong Han (Arabian Journal of Geosciences, 2021)

Green-synthesized nanosize Mont-supported Fe0 via tea extract for enhanced transport and in situ remediation of Pb(II) in soil - Han Yang; Zhi Ye; Fang Feng; Nan Xu; Jing Yang; Zihan Yao; Zuling Li; Jianping Chen (Journal of Soils and Sediments, 2021)

A novel approach to simulating debris flow runout via a three-dimensional CFD code: a case study of Xiaojia Gully - Yansong Zhang; Jianping Chen; Chun Tan; Yiding Bao; Xudong Han; Jianhua Yan; Qaiser Mehmood (Bulletin of Engineering Geology and the Environment, 2021)

Numerical simulation and analysis of a geological disaster chain in the Peilong valley, SE Tibetan Plateau - Zhihai Li; Fujun Zhou; Xudong Han; Jianping Chen; Yuchao Li; Shijie Zhai; Mengxia Han; Yiding Bao (Bulletin of Engineering Geology and the Environment, 2021)

Comprehensive Marine Observing Experiment Based on High-Altitude Large Unmanned Aerial Vehicle (South China Sea Experiment 2020 of the “Petrel Project”) - Xuefen Zhang; Liangxu Li; Rongkang Yang; Ran Guo; Xia Sun; Jianping Luo; Hongbin Chen; Daxin Liu; Kebing Tang; Wenwu Peng; Xiaodong Han; Qiyun Guo; et al. (Advances in Atmospheric Sciences, 2021)

Investigation of geometrical representative elementary volumes based on sampling directions and fracture sets - Ying Liu; Qing Wang; Jianping Chen; Xudong Han; Shengyuan Song; Yunkai Ruan (Bulletin of Engineering Geology and the Environment, 2021)

MicroRNA-20a-5p suppresses tumor angiogenesis of non-small cell lung cancer through RRM2-mediated PI3K/Akt signaling pathway - Junlei Han; Jianping Hu; Fang Sun; Hongzhi Bian; Bingxiang Tang; Xiang Fang (Molecular and Cellular Biochemistry, 2021)

Complete genome sequence of a new achyranthes virus A isolate from Achyranthes bidentata in China - Xinyang Wu; Yuchao Lai; Lanqing Lv; Kelei Han; Ziqiang Chen; Yuwen Lu; Jiejun Peng; Lin Lin; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2021)

Landslide susceptibility mapping along the upper Jinsha River, south-western China: a comparison of hydrological and curvature watershed methods for slope unit classification - Xiaohui Sun; Jianping Chen; Xudong Han; Yiding Bao; Xin Zhou; Wei Peng (Bulletin of Engineering Geology and the Environment, 2020)

Correction to: Preconditioning with VEGF Enhances Angiogenic and Neuroprotective Effects of Bone Marrow Mononuclear Cell Transplantation in a Rat Model of Chronic Cerebral Hypoperfusion - Jianping Wang; Xiaojie Fu; Lie Yu; Nan Li; Menghan Wang; Xi Liu; Di Zhang; Wei Han; Chenguang Zhou; Jian Wang (Molecular Neurobiology, 2020)

Debris Flow Susceptibility Assessment and Runout Prediction: A Case Study in Shiyang Gully, Beijing, China - Yongchao Li; Jianping Chen; Yiwei Zhang; Shengyuan Song; Xudong Han; Muhammad Ammar (International Journal of Environmental Research, 2020)

The response of warm-season precipitation extremes in China to global warming: an observational perspective from radiosonde measurements - Jianping Guo; Yan Yan; Dandan Chen; Yanmin Lv; Yi Han; Xiaoran Guo; Lin Liu; Yucong Miao; Tianmeng Chen; Ji Nie; Panmao Zhai (Climate Dynamics, 2020)

Study on Pollution Characterization and Source Apportionment of Daytime and Nighttime PM2.5 Samples in an Urban Residential Community in Different Weather Conditions - Yan Zhao; Lihong Feng; Yuwen Wang; Bodong Shang; Jianping Li; Penghao Han (Bulletin of Environmental Contamination and Toxicology, 2020)

Deep origin of Cenozoic volcanoes in Northeast China revealed by 3-D electrical structure - Shiwen Li; Aihua Weng; Jianping Li; Xuanlong Shan; Jiangtao Han; Yu Tang; Yanhui Zhang; Xueqiu Wang (Science China Earth Sciences, 2020)

Characterization of a Saccharum spontaneum with a basic chromosome number of x = 10 provides new insights on genome evolution in genus Saccharum - Zhuang Meng; Jinlei Han; Yujing Lin; Yiyong Zhao; Qingfang Lin; Xiaokai Ma; Jianping Wang; Muqing Zhang; Liangsheng Zhang; Qinghui Yang; Kai Wang (Theoretical and Applied Genetics, 2020)

Application of a GIS-based slope unit method for landslide susceptibility mapping along the rapidly uplifting section of the upper Jinsha River, South-Western China - Xiaohui Sun; Jianping Chen; Xudong Han; Yiding Bao; Jiewei Zhan; Wei Peng (Bulletin of Engineering Geology and the Environment, 2020)

Accumulation of salicylic acid-elicited alkaloid compounds in in vitro cultured Pinellia ternata microtubers and expression profiling of genes associated with benzoic acid-derived alkaloid biosynthesis - Yongbo Duan; Han Zhang; Xue Meng; Mingmei Huang; Zeyu Zhang; Chenhao Huang; Fenglan Zhao; Tao Xue; Jianping Xue (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Short-term exposure to ambient air pollution and daily atherosclerotic heart disease mortality in a cool climate - Guangcong Liu; Baijun Sun; Lianzheng Yu; Jianping Chen; Bing Han; Bo Liu; Jie Chen (Environmental Science and Pollution Research, 2019)

TLR2 gene in seahorse brood pouch plays key functional roles in LPS‐induced antibacterial responses - Bo Zhang; Huixian Zhang; Geng Qin; Yuhong Liu; Xue Han; Jianping Yin; Qiang Lin (Journal of Fish Diseases, 2019)

Rapid identification of a candidate nicosulfuron sensitivity gene (Nss) in maize (Zea mays L.) via combining bulked segregant analysis and RNA-seq - Xiaomin Liu; Bo Bi; Xian Xu; Binghua Li; Shengmin Tian; Jianping Wang; Hui Zhang; Guiqi Wang; Yujun Han; J. Scott McElroy (Theoretical and Applied Genetics, 2019)

Flash flood schlep ability estimation in vertical distribution law of the precipitation area: a case of Xulong gully, Southwest China - Xiaohui Sun; Jianping Chen; Yiding Bao; Xudong Han; Jiewei Zhan; Wei Peng (Arabian Journal of Geosciences, 2019)

Natural and synthetic flavonoids, novel blockers of the volume-regulated anion channels, inhibit endothelial cell proliferation - Yucong Xue; Honglin Li; Yuanyuan Zhang; Xue Han; Gaohua Zhang; Wenya Li; Huiran Zhang; Yue Lin; Pingping Chen; Xiaorun Sun; Yalei Liu; Li Chu; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Runout analysis of a potential debris flow in the Dongwopu gully based on a well-balanced numerical model over complex topography - Xudong Han; Jianping Chen; Peihua Xu; Cencen Niu; Jiewei Zhan (Bulletin of Engineering Geology and the Environment, 2018)

A well-balanced numerical scheme for debris flow run-out prediction in Xiaojia Gully considering different hydrological designs - Xudong Han; Jianping Chen; Peihua Xu; Jiewei Zhan (Landslides, 2017)

Automatic Identification of Rock Fracture Sets Using Finite Mixture Models - Jiewei Zhan; Jianping Chen; Peihua Xu; Wen Zhang; Xudong Han; Xin Zhou (Mathematical Geosciences, 2017)

Effects of salvianolic acid B on L-type calcium channels and myocardial contractility in isolated rat ventricular myocytes and hERG K+ channels expressed in HEK293 cells - Qiongtao Song; Xue Han; Yuchong Xue; Tao Song; Xi Chu; Xuan Zhang; Yuanyuan Zhang; Ying Zhang; Jianping Zhang; Li Chu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Complete genomic characterization of milk vetch dwarf virus isolates from cowpea and broad bean in Anhui province, China - Chenhua Zhang; Hongying Zheng; Dankan Yan; Kelei Han; Xijiao Song; Yong Liu; Dongfang Zhang; Jianping Chen; Fei Yan (Archives of Virology, 2017)

Physical and chemical properties of sound-producing and soundless sand particles from booming sand dunes, northern China - Fei Han; Mingzhong Tian; Fadong Wu; Jianping Zhang; Siwen Liu; Lulin Wang (Arabian Journal of Geosciences, 2017)

Preconditioning with VEGF Enhances Angiogenic and Neuroprotective Effects of Bone Marrow Mononuclear Cell Transplantation in a Rat Model of Chronic Cerebral Hypoperfusion - Jianping Wang; Xiaojie Fu; Lie Yu; Nan Li; Menghan Wang; Xi Liu; Di Zhang; Wei Han; Chenguang Zhou; Jian Wang (Molecular Neurobiology, 2016)

A 3D Fracture Network Model for the Undisturbed Rock Mass at the Songta Dam Site Based on Small Samples - Xudong Han; Jianping Chen; Qing Wang; Yanyan Li; Wen Zhang; Tianwen Yu (Rock Mechanics and Rock Engineering, 2016)

USP11, Deubiquitinating Enzyme, Associated with Neuronal Apoptosis Following Intracerebral Hemorrhage - Zhiwei Xu; Xiaohong Li; Jianping Chen; Jianmei Zhao; Jun Wang; Yuhong Ji; Yifen Shen; Lijian Han; Jiansheng Shi; Dongmei Zhang (Journal of Molecular Neuroscience, 2016)

Development of an agroinoculation system for full-length and GFP-tagged cDNA clones of cucumber green mottle mosaic virus - Hongying Zheng; Caili Xiao; Kelei Han; Jiejun Peng; Lin Lin; Yuwen Lu; Li Xie; Xiaohua Wu; Pei Xu; Guojing Li; Jianping Chen; Fei Yan (Archives of Virology, 2015)

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

Nitric oxide mediates hypocrellin accumulation induced by fungal elicitor in submerged cultures of Shiraia bambusicola - Wen Du; Jiandong Liang; Yanfeng Han; Jianping Yu; Zongqi Liang (Biotechnology Letters, 2015)

Advances in longitudinal studies of amnestic mild cognitive impairment and Alzheimer’s disease based on multi-modal MRI techniques - Zhongjie Hu; Liyong Wu; Jianping Jia; Ying Han (Neuroscience Bulletin, 2014)

Structural modal parameter identification and damage diagnosis based on Hilbert-Huang transform - Jianping Han; Peijuan Zheng; Hongtao Wang (Earthquake Engineering and Engineering Vibration, 2014)

Effects of microbial elicitor on production of hypocrellin by Shiraia bambusicola - Wen Du; Zongqi Liang; Xiao Zou; Yanfeng Han; Jiandong Liang; Jianping Yu; Wanhao Chen; Yurong Wang; Chunlong Sun (Folia Microbiologica, 2013)

A numerical simulation of aerosols’ direct effects on tropopause height - Jian Wu; Yanyan Xu; Qian Yang; Zhiwei Han; Deming Zhao; Jianping Tang (Theoretical and Applied Climatology, 2013)

Antibacterial activity of hypocrellin A against Staphylococcus aureus - Wen Du; Chunlong Sun; Zongqi Liang; Yanfeng Han; Jianping Yu (World Journal of Microbiology and Biotechnology, 2012)

Nutrient dynamics and biological consumption in a large continental shelf system under the influence of both a river plume and coastal upwelling - Aiqin Han; Minhan Dai; Shuh-Ji Kao; Jianping Gan; Qing Li; Lifang Wang; Weidong Zhai; Lei Wang (Limnology and Oceanography, 2012)
We examined the dynamics of dissolved inorganic nitrogen (DIN, nitrate + nitrite), dissolved inorganic phosphorus (DIP), and silicate (Si(OH) 4 ) in the northern shelf of the South China Sea in summer, which is under a complex hydrodynamic scheme largely shaped by river plume and coastal upwelling, along with the enhanced biological consumption of nutrients therein. The Pearl River plume, with high nutrient concentrations (∼ 0.1–14.2 µmol L −1 for DIN, ∼ 0.02–0.10 µmol L −1 for DIP, and ∼ 0.2–18.9 µmol L −1 for Si(OH) 4 ), occupied a large area of the middle shelf (salinity 4 concentrations dropped to −1 , ∼ 0.02–0.03 µmol L −1 , and ∼ 2.0 µmol L −1 , respectively. A three end‐member mixing model was constructed based on potential temperature and salinity conservation to assess biological consumption of inorganic nutrients, which was denoted by Δ and defined by the deviation from conservative mixing. In the coastal upwelling zone and deep chlorophyll maximum layer, the nutrient uptake ratio ΔDIN : ΔDIP was 16.7, which is the classic Redfield ratio. In contrast, in the river plume the uptake ratio was 61.3 ± 8.7. We believed that an alternative non‐DIP source likely contributed to this higher DIN : DIP consumption ratio in the river plume regime. Meanwhile, Si(OH) 4 showed predominant consumption in the river plume and a combination of regeneration and consumption along the path of the coastal upwelling current.

Seasonal variations in heavy metals concentrations in Mt. Qomolangma Region snow - Jianping Duan; Lily Wang; Jiawen Ren; Lun Li; Junqing Han (Journal of Geographical Sciences, 2009)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)